2011
DOI: 10.1002/bdd.742
|View full text |Cite
|
Sign up to set email alerts
|

1α,25‐Dihydroxyvitamin D3 on intestinal transporter function: studies with the rat everted intestinal sac

Abstract: Previous studies have shown that 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3) treatment (2.56 nmol/kg i.p. daily×4) increased PepT1, Mrp2, Mrp4, Asbt, but not Mdr1/P-gp in the rat small intestine. In this study, the intestinal everted sac technique, together with various select probes: mannitol (paracellular transport), glycylsarcosine (PepT1), 5(and 6)-carboxy-2',7'-dichlorofluorescein (CDF) diacetate (precursor of CDF for Mrp2), adefovir dipivoxil (precursor of adefovir for Mrp4) and digoxin (P-gp) was used to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 56 publications
3
24
1
Order By: Relevance
“…Then, the intracellularly generated adefovir is absorbed into the blood by crossing the basolateral membrane of enterocytes primarily via MRP4/Mrp4-mediated efflux rather than by passive diffusion, due to the highly negative charge of adefovir. 13,15,17) Consistent with this, our previous in vitro study using everted Since adefovir dipivoxil is a substrate of P-gp, and its intestinal permeation can be limited by P-gp-mediated efflux, 30) we could not rule out the regulation of P-gp function by 1,25(OH) 2 D 3 treatment. However, when the effects of 1,25(OH) 2 D 3 on the intestinal absorption of adefovir dipivoxil in rat duodenum, jejunum and ileum segments were observed using the in situ closed loop technique (Fig.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Then, the intracellularly generated adefovir is absorbed into the blood by crossing the basolateral membrane of enterocytes primarily via MRP4/Mrp4-mediated efflux rather than by passive diffusion, due to the highly negative charge of adefovir. 13,15,17) Consistent with this, our previous in vitro study using everted Since adefovir dipivoxil is a substrate of P-gp, and its intestinal permeation can be limited by P-gp-mediated efflux, 30) we could not rule out the regulation of P-gp function by 1,25(OH) 2 D 3 treatment. However, when the effects of 1,25(OH) 2 D 3 on the intestinal absorption of adefovir dipivoxil in rat duodenum, jejunum and ileum segments were observed using the in situ closed loop technique (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…15) However, changes in the expression and/or in vitro functions of drug transporters do not always correlate with the fates of therapeutic agents in the whole body system. Therefore, further studies are needed on the effects of 1,25(OH) 2 D 3 on transporter substrate drug pharmacokinetics in animals or humans.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that a number of genes encoding intestinal membrane transporters for both endogenous substances and drugs and xenobiotics are regulated by vitamin D 3 and VDR Fan et al, 2009;Tachibana et al, 2009;Chow et al, 2010;Maeng et al, 2011). We have investigated whether vitamin D 3 and VDR regulate the expression of the SLCO1A2 gene, which encodes an important membrane transporter for intestinal absorption of numerous drugs.…”
Section: Introductionmentioning
confidence: 99%